Smokers' Neurological Responses to Novel and Repeated Health Warning Labels (HWLs) From Cigarette Packages - Fridriksson, Johann F.; Rorden, Chris; Newman-Norlund, Roger D.; Froeliger, Brett; Thrasher, James F. (Frontiers in Psychiatry, 2018)
Graphic health warning labels (HWLs) depicting bodily injury due to smoking are effective for producing changes in affect, cognition and smoking behavior in adult smokers. However, little is known about the effects of repeated presentation of graphic HWL's on the aforementioned processes. The goal of this study was to examine neural and behavioral responses to graphic HWL's and evaluate whether the repeated presentation of graphic HWL's leads to repetition suppression (RS). Smokers (N = 16) performed an event-related HWL cue task while blood oxygen level dependent (BOLD) signal was collected during a functional magnetic resonance imaging (fMRI) experimental session. Consistent with prior literature, graphic HWL's, as compared to scrambled images, elicited increased BOLD response in brain regions involved in self-referential and emotion processing. Importantly, BOLD response at sites in this network diminished during repeated presentation of the same HWL. These findings suggest that while novel graphic HWL's may have a significant effect on smokers' brain activity, repeated presentation may lead to muted responses and thus limit their potential to induce behavioral change.